Factors influencing appearance appeals for decreasing unsafe tanning behaviors - Entringer, Aaron (Kansas State University, 2017)
In a two-study thesis, the current project compares the effectiveness of various messages aimed at reducing unsafe high-end tanning behaviors. Study 1 used messages focused on either the appearance or health consequences of tanning in an effort to reduce the intention of unsafe high-end tanning behaviors. The results indicated that participants did not differ in their high-end sun tanning frequencies as a result of the message condition, but that there was an interaction effect between message type and gender, such that appearance messages were most effective at reducing unsafe tanning behaviors for females. However, upon further examination of the appearance messages, it was noted that there were two primary aspects of appearance content that were present: aging and blemishes. Therefore, Study 2 examined whether the gender effect that was present in Study 1 was being driven by either the aging or blemish content of the messages. Surprisingly, it was found in Study 2 that aging messages were more effective on male participants than female participants at reducing intention of unsafe high-end tanning behaviors. Additionally, it was found in Study 2 that graphic images effectively decreased intention to perform unsafe high-end tanning behaviors. These findings along with their implications are discussed.
Keywords: Tanning; Appearance; Health; Aging; Blemishes; Graphic image use